EL NACIMIENTO DE LA PATOLOGÍA Y SU DESARROLLO EN LA REGIÓN (The birth of the pathology and its development in the region) - Giraldo Giraldo, Cesar Augusto (CES Medicina, 2011)
Se presenta una rápida visión del surgimiento de los conceptos relacionados con la patología desde los tiempos de los griegos y los romanos hasta llegar al nacimiento de la disciplina con los aportes de Xavier Bichat. En relación al nacimiento de la disciplina en Colombia se narran sus inicios y las contribuciones del Doctor Alfredo Correa Henao. Abstract: It is presente and overview of the emergence of concepts related to the pathology since the time of the Greeks and Romans up to the birth of the discipline with the contributions from Xavier Bichat. In relation to the birth of the discipline in Colombia is described their development and the contributions of Dr. Alfredo Correa Henao.